O papel da controladoria em uma agroindústria : um estudo de caso - Colnaghi, Vinícius Winter (2022)
The theme to be easily understood in this work is Controllership, a young branch in the area of Accounting. This new branch has been of great help to organizations by subsidizing information to managers to assist them in decision-making and to fulfill several other functions. Therefore, the question of this research is: How is the Controllership of the company ABC meeting Contingency Situations and Information Needs? The main objective of this work is to verify which functions the controllership of the industry object of this study is carrying out and if it is able to meet the environmental contingencies. This research is a case study, of the descriptive type of an agribusiness company, with a qualitative approach. The role of controllership in the business environment was identified, as well as a controller designed for the company's controllers and directors to verify how it is meeting contingencies and thus identify how they objectively meet the company's business. The organization object of this study is an agroindustry located near Passo Fundo, Rio Grande do Sul, which seeks to remain competitive in the market and has been restructuring itself in recent decades, with the support of the controllership sector. It was found that there is a certain need for improvement in the quality and quantity of information provided by the Comptroller, as well as the need for it to adapt to meet certain political contingencies.